Determinan niat beli produk perawatan diri organik - Chrisvinlya, Chrisvinlya; Cokki, Cokki (Universitas Tarumanagara, 2023)
This study determined the influence of product knowledge and perceived value on organic personal care purchase intention. Examined the attitude towards purchase intention as the mediator of product knowledge and perceived value towards purchase intention also perceived behavioral control as a moderator between attitude towards purchase intention and organic personal care purchase intention which is the difference of TPB application in previous and still limited. A total of 351 respondents participated in this study by online survey who knows about organic personal care. The collected data is used to examine the correlation of variables by the PLS-SEM method, and the result showed organic personal care purchase intention is influenced by attitude towards purchase intention and perceived behavioral control. Attitude toward purchase intention is influenced by product knowledge (subjective and objective knowledge) and perceived value (health and environmental value). Marketers need to carry out the event, give a sample, and laboratory tests for organic personal care products to inform product perceived value and increase subjective and objective knowledge, also the attitude towards organic personal care product purchase intention. Studi ini menentukan pengaruh dari pengetahuan produk dan nilai yang dipersepsikan terhadap niat beli produk perawatan diri organik. Selain itu, sikap sebagai mediator antara pengetahuan produk dan nilai yang dipersepsikan dengan niat beli, dan persepsi kontrol perilaku sebagai moderasi antara sikap dengan niat beli yang membedakan penerapan teori TPB pada penelitian sebelumnya dan masih terbatas. Data yang diperoleh berasal dari 351 responden mengetahui produk perawatan diri organik. Teknik analisa data menggunakan PLS-SEM dalam menguji keterkaitan antar variabel yang diteliti. Niat beli produk perawatan diri organik dipengaruhi oleh sikap terhadap niat beli dan persepsi kontrol perilaku. Sikap terhadap niat beli produk perawatan diri organik dipengaruhi oleh pengetahuan produk yang mencakupi pengetahuan subjektif dan pengetahuan objektif, serta nilai-nilai produk yang dipersepsikan, seperti nilai kesehatan dan nilai lingkungan. Tim pemasar perlu melakukan event, memberikan sampel, dan melakukan tes laboratorium terhadap produk perawatan diri organik untuk menginformasikan nilai-nilai produk yang dipersepsikan, meningkatkan pengetahuan subjektif maupun objektif, dan sikap terhadap niat beli produk perawatan diri organik.